Isolation of Mutations in the Catalytic Domain of the Snf1 Kinase That Render Its Activity Independent of the Snf4 Subunit - Leech, Anna (American Society for Microbiology, 2003)
Activation of the Snf1 kinase requires at least two events, phosphorylation of the activation loop on threonine 210 and an Snf4-dependent process that is not completely defined. Snf4 directly interacts with a region of the regulatory domain of Snf1 that may otherwise act as an autoinhibitory domain. In order to gain insight into the regulation of Snf1 kinase by Snf4, deletions in the regulatory domain of the catalytic subunit were engineered and tested for their effect on Snf1 function in the absence of Snf4. Deletion of residues 381 to 488 from the Snf1 protein resulted in a kinase that was activated by glucose limitation even in the absence of the Snf4 protein. A larger deletion (amino acids 381 to 608) encompassing virtually the entire regulatory domain resulted in complete inactivation of the Snf1 kinase even in the presence of Snf4. A genetic screen for amino acid substitutions that conferred an Snf4-independent phenotype identified four point mutations in the Snf1 catalytic domain. One very conservative mutation, leucine 183 to isoleucine, conferred nearly wild-type levels of Snf1 kinase function in the absence of the Snf4 protein. Purified Snf1 kinase was inactive when isolated from snf4Δ cells, whereas the Snf1-L183I kinase exhibited significant activity in the absence of Snf4. Our data support the idea that Snf1 kinase activity is constrained in cis by an autoinhibitory domain and that the Snf4-mediated activation of Snf1 can be bypassed by subtle conformational changes in the catalytic domain of the Snf1 kinase.